2005
DOI: 10.1167/iovs.04-1225
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Keratocytes: Phenotypic and Species Differences in Abundant Protein Expression and In Vitro Light-Scattering

Abstract: Abundant protein expression is a characteristic feature of corneal keratocytes that is lost when cells are phenotypically modulated in culture. Greater light-scattering by myofibroblasts also provides support for a link between cellular transparency and haze after injury that is possibly related to loss of protein expression or development of prominent actin filament bundles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
127
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 30 publications
0
127
0
1
Order By: Relevance
“…The corneal myofibroblast phenotype present during wound healing is characterized by the expression of ␣-smooth muscle actin (␣-SMA), a filamentous protein that plays a role in the matrix contraction (9). Cultured rabbit corneal myofibroblasts scatter more light than keratocytes and exhibit reduced expression of both TKT and ALDH1 (16). A recent study in human cells corroborates the rabbit studies: ALDH3 and TKT are both reduced in repair fibroblast and myofibroblast populations compared with the quiescent keratocyte (17).…”
mentioning
confidence: 72%
“…The corneal myofibroblast phenotype present during wound healing is characterized by the expression of ␣-smooth muscle actin (␣-SMA), a filamentous protein that plays a role in the matrix contraction (9). Cultured rabbit corneal myofibroblasts scatter more light than keratocytes and exhibit reduced expression of both TKT and ALDH1 (16). A recent study in human cells corroborates the rabbit studies: ALDH3 and TKT are both reduced in repair fibroblast and myofibroblast populations compared with the quiescent keratocyte (17).…”
mentioning
confidence: 72%
“…Additional study is needed to determine what factors are most important. We speculate that differences in the timing of myofibroblast appearance in the wounded corneas of different species are due to differences in marker protein expression, such as alpha smooth muscle actin, in the stroma of different species, based on the study performed by Jester and his coworkers (Jester et al 2005) that showed human, mouse, rabbit, chicken and pig corneal keratocytes have diverse protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,28 Growth factor-stimulated rabbit keratocytes in culture also show significantly reduced levels of crystallin protein and increased cellular light scattering, with TGF␤-induced myofibroblasts showing the greatest changes. 22 Although expression of corneal crystallins has been shown to correlate with cellular light scattering and corneal haze, the molecular and biophysical mechanisms affecting cellular transparency have yet to be explained. In this study, we evaluated the biophysical characteristics of keratocytes and myofibroblasts on the basis of cell size, protein content, expression of corneal crystallins, and changes in light scattering after induced corneal crystallin expression.…”
mentioning
confidence: 99%